Recycling and refilling of transmitter quanta at the frog neuromuscular junction - Van der Kloot, William (Blackwell Science Inc, 2000)
1. Fluorescent dyes have been used at the frog neuromuscular junction to label synaptic vesicular membrane. Retrieved membrane is reformed into vesicles, which are released along with pre-existing vesicles. Consequently, if vesicular refilling with acetylcholine (ACh) is depressed by inhibitors, two sizes of quanta should be released: normal and smaller. As recycling continues the fraction of smaller size quanta should increase exponentially. 2. We enhanced the rate of quantal release by elevating the K(+) concentration. The principal inhibitors were (−)-vesamicol (VES), hemicholinium-3 (HC3), and NH(4)(+). Quantal size measurements were fitted to one and to two cumulative lognormal probability distribution functions. When two fitted better, the statistical significance assessment took into account the three additional parameters used in calculating the fit. 3. After recycling in the presence of inhibitor, many sets were fitted better by two lognormal functions. As recycling continued, the fraction of the miniature endplate potential voltage–time integrals (∫MEPPs) in the larger sub-population decreased exponentially. 4. The size of the releasable pool was estimated by counting the quanta released by carbonyl cyanide m-chlorophenylhydrazone (CCCP). This was compared to pool sizes calculated from the inhibitor experiments. The two estimates of pool size were indistinguishable, with mean values ranging from about 170 000 to 270 000. 5. With all of the treatments tested, the means of the sizes in the smaller sub-population of ∫MEPPs were about 1/3 those of the larger sub-populations. 6. Recycling synaptic vesicles appear to be incorporated into the releasable pool from which they have roughly the same probability of release as the pre-existing vesicles.